Effect of total glycosides of Cistanche deserticola on the energy metabolism of human HepG2 cells - Feng, Duo; Zhou, Shi-qi; Zhou, Ya-xi; Jiang, Yong-jun; Sun, Qiao-di; Song, Wei; Cui, Qian-qian; Yan, Wen-jie; Wang, Jing (Frontiers in Nutrition, 2023)
Abstract: To study the anti-tumor effect of Cistanche deserticola Y. Ma, in this experiment, HepG2 cells were treated with 0, 3.5, 10.5, 21, 31.5 and 42 μg/mL total glycosides (TG) of Cistanche deserticola. The HepG2 cell survival rate and 50% inhibition concentration were detected by CCK-8 method, and the level of Reactive oxygen species (ROS) was detected by DCFH-DA fluorescence probe. Finally, Seahorse XFe24 energy analyzer was used to detect cell Mitochondrial pressure and Glycolytic pressure. The results showed that TG could reduce the survival rate of HepG2 cells, and the IC50 was 35.28 μg/mL. With the increase of concentration, the level of ROS showed an upward trend and was concentration dependent. Energy metabolism showed that each dose group of TG could significantly decline the mitochondrial respiratory function and glycolytic function of HepG2 cells. In a conclusion, TG could significantly inhibit the mitochondrial respiration and glycolysis ability of HepG2 cells, increase the level of ROS and inhibit cell proliferation. Thus, this experiment pointed out that Cistanche deserticola can be used as a source of anti-cancer foods or drugs in the future, but further research is needed in its mechanism research and clinical application.